Climate-Smart Pathways for Wheat-Rice Farming in the Indo-Gangetic Plains (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Climate-smart agriculture (CSA) is an approach designed to transform agricultural systems so that it can respond effectively to climate variability while ensuring long-term food security and sustainable development in Agriculture. The framework emphasizes restructuring of agricultural practices and also institutions to address climate-related risks while maintaining productivity. The three central pillars of CSA include sustainable enhancement of agricultural output and farm income, focusing on the strengthening adaptation and resilience to climate change, and reducing greenhouse gas (GHG) emissions wherever feasible.CSA focuses on promoting the development of context-specific agricultural strategies that will help in maintaining food security under changing climatic conditions while conserving natural resources. CSA supports informed decision-making across multiple levels like—from farmers to policymakers—by identifying locally appropriate and environmentally sound practices. In the Indo-Gangetic Plains (IGP), the wheat–rice cropping system has been important in national food security but this now faces serious sustainability challenges due to various issues like, declining water resources, degradation of soil, shortages of labour, and rising energy demands. Based on a critical review of existing literature, this paper outlines climate-smart strategies for restructuring the wheat–rice system to improve productivity, resilience, and environmental sustainability in the IGP.